2021
DOI: 10.1111/jasp.12804
|View full text |Cite
|
Sign up to set email alerts
|

They’re (not) playing our song: (Ir)religious identity moderates the effects of listening to religious music on memory, self‐esteem, and mood

Abstract: Previous research suggests that listening to music can enhance memory and well‐being. However, what is often missing from this analysis is consideration of the social dimensions of music—for example, its capacity to affirm or threaten listeners’ social identities. This study examined whether (ir)religious music that was potentially identity‐affirming or identity‐threatening (Christian hymns, Buddhist chants, classical, or no music) would affect Christians’ and Atheists’ (N = 267) well‐being and memory performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 93 publications
(122 reference statements)
1
3
0
Order By: Relevance
“…The ndings from the qualitative data analysis also suggest that members of underrepresented groups may feel hostility towards information that doesn't align with their personal experiences. This research supplements prior studies demonstrating the importance of individuals' relationship to music (10,13) by pointing to the importance of socio-cultural variables as important factors in uencing cognitive tasks.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The ndings from the qualitative data analysis also suggest that members of underrepresented groups may feel hostility towards information that doesn't align with their personal experiences. This research supplements prior studies demonstrating the importance of individuals' relationship to music (10,13) by pointing to the importance of socio-cultural variables as important factors in uencing cognitive tasks.…”
Section: Discussionsupporting
confidence: 77%
“…For example, Ysseldyk and colleagues found that listening to music that threatens one's religious identity can undermine performance on memory tasks and contribute to increased feelings of hostility. Meanwhile, music that is consistent with one's social identity can promote positive cognitive and social responses (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies, both observed and experimental, have demonstrated the widespread benefits of music and its influence on various aspects of human existence, including physical, sociocultural, academic, psychological, and emotional well-being (Särkämö et al, 2014;Rose et al, 2019;Whiteman, 2020;Oliver et al, 2021). Music has also been utilized in prior research to investigate individuals' preferences and behaviors (Kim and Kang, 2021;Greenberg et al, 2022); as well as its therapeutic effects on mental health and other ailments (Ysseldyk et al, 2021). Studies focusing on music and its types have shown potential for reducing stress and improving well-being in youngsters, particularly in young students (Saarikallio et al, 2020).…”
Section: Moderated Mediation Role Music Typementioning
confidence: 99%